Constructing Ambient Intelligence AmI 2008 Workshops, Nuremberg, Germany, November 19-22, 2008, Revised Papers - Gerhäuser, Heinz; Hupp, Jürgen; Efstratiou, Christos; Heppner, Janina (Communications in Computer and Information Science,, 2009)
Ambient intelligence (AmI) was established in the late 1990s as a recent paradigm for electronic environments for the timeframe of 2010-2020. AmI is essentially an elabo- tion of Mark Weiser's vision of ubiquitous computing. Weiser was aiming at a novel mobile computing infrastructure integrated into the networked environment of people. AmI is the idea of a technology that will become invisibly embedded in our natural s- roundings, present whenever we need it, enabled by simple and effortless interaction, attuned to all our senses, adaptive to users, context-sensitive, and autonomous. AmI refers to smart electronic environments that are sensitive and responsive to the presence of people. Since its adoption the vision has grown and fully developed, bec- ing quite influential in the development of novel ideas for information processing and new concepts for multi-disciplinary fields including electrical engineering, computer science, industrial design, user interfaces, and cognitive sciences. The AmI system - fords a basis for new paradigms of technological innovation within a multi-dimensional society. The added value of the AmI vision is the fact that the large-scale integration of electronics into the environment allows the actors, i. e. , people and objects, to collaborate with their surroundings in a natural measure. This is directly related to the increasing societal demand for communication and the exchange of information.